2018
DOI: 10.3389/fped.2018.00045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tactile Stimulation on Termination and Prevention of Apnea of Prematurity: A Systematic Review

Abstract: Apnea of prematurity (AOP) is one of the most common diagnoses in preterm infants. Severe and recurrent apneas are associated with cerebral injury and adverse neurodevelopmental outcome. Despite pharmacotherapy and respiratory support to prevent apneas, a proportion of infants continue to have apneas and often need tactile stimulation, mask, and bag ventilation and/or extra oxygen. The duration of the apnea and the concomitant hypoxia and bradycardia depends on the response time of the nurse. We systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…Although different forms of manual and mechanical tactile stimulation can prevent or terminate apnoea, 13 their effectiveness could well be technique and/or locationdependent. Several studies have hypothesised that tactile stimulation exerts its effect on the respiratory centre via activation of cutaneous nerves 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Although different forms of manual and mechanical tactile stimulation can prevent or terminate apnoea, 13 their effectiveness could well be technique and/or locationdependent. Several studies have hypothesised that tactile stimulation exerts its effect on the respiratory centre via activation of cutaneous nerves 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Richter and Ostovar [38] identified 157 publications on rocking in the medical literature between 1948 and 2014. In a systematic review of 15 articles published between 1970 and 2017 on the effect of manual and mechanical tactile stimulation on apnea in preterm infants, Cramer et al [59] found seven articles on rhythmical stimulations, essentially with water mattresses. Korner et al used waterbeds to reduce apnea in preterm infants.…”
Section: Rhythmic Vestibular Stimulationmentioning
confidence: 99%
“…Mechanical limb stimulation has been associated with shorter durations of AOP (Smith et al, 2015). There are two methods of tactile limb stimulation: manual and mechanical (Cramer et al, 2018). The manual method of tactile stimulation relies on massaging the limbs of the infants while the automatic method of tactile stimulation includes closed-loop pulsating or vibrating systems (Cramer et al, 2018;Frank, Bordiuk, Borromeo-McGrail, Saltzman, & Keitel, 1973;Lovell et al, 1999;Pichardo, Adam, Rosow, Bronzino, & Eisenfeld, 2003).…”
Section: Apnea Of Prematuritymentioning
confidence: 99%
“…Further studies with larger sample sizes need to be conducted to definitively establish limb stimulation as primary interventional treatment for AOP. In addition, more research focused on the afferent/efferent neural pathways that link limb stimulation to the respiratory system is needed to optimize tactile stimulation treatments for AOP over long periods of time in the NICU (Cramer et al, 2018). A highly promising pharmacological alternative to caffeine treatment is the use of ampakines to reduce the frequency of apneic episodes and increase respiratory drive (Ren, Poon, Tang, Funk, & Greer, 2006).…”
Section: Apnea Of Prematuritymentioning
confidence: 99%